Studi Kasus: Evaluasi Status Hemodinamik Pasien Dengan Ventilator Mekanik Pasca Mobilisasi Harian (Supinasi - Lateral) di Ruang ICU RSUD Ulin Banjarmasin - Ifa Hafifah; Fajar Rizki Rahayu; Lukmannul Hakim (Faletehan Health Journal, 2021)
Changes of patient’s position are routinely used in intensive care unit. The purpose of positioning is not only to increase oxygen transportation but also for prophylaxis and comfort priority, to prevent from ulcer, and to reduce deep vein thrombosis incidence, pulmonary embolism, atelectasis and pneumonia. The aim of the study was to describe hemodynamic status of patients with mechanical ventilator, who changed position from supine to lateral position at the ICU of Ulin Banjarmasin General Hospital. This study used pre-experimental design with one-shot case study. This study had 5 respondents. The result showed changes in the patients’ hemodynamic status (blood pressure, mean arterial pressure, respiration rate, and pulse rate) from supine to lateral position. Furthermore, there were significant changes in 3 of 5 respondents in mean arterial pressure and 2 of 5 respondents in respiration rate. Positioning patients with mechanical ventilators from supine to lateral position can lead to an increase or a decrease of hemodynamic status. The nurses were expected to be able to do a close monitoring while positioning patients with mechanical ventilator.